THE CONCEPT OF SOCIAL RESPONSIBILITY DISCLOSURES FOR ISLAMIC BANKS BASED ON SHARI’AH ENTERPRISE THEORY - Intan Meutia (Universitas Brawijaya, 2010)
Abstract. The Concept of Social Responsibility Disclosures for Islamic Banks based on Shari’ah Enterprise Theory. This research aims to develop the concept and characteristics of social responsibility disclosure and items for the social responsibility disclosure of Islamic banks. This research was conducted based on the critical paradigm by using Habermas’s Theory of Communication Action extended to spirituality in understanding social reality. This study also uses Shari’ah Enterprise Theory to analyze and to produce the concept of social responsibility disclosure for Islamic banks. Analysis was conducted on the annual reports of three Islamic banks in Indonesia, Bank Mega Syariah, Bank Syariah Mandiri and Bank Muamalat Indonesia. Interviews with stakeholders, including direct and indirect stakeholders were also conducted. Spiritual values were found during the research. These values are sharing, rahmatan lil alamin and maslaha. These values are used as guidance in developing items of social responsibility disclosure. Furthermore, a concept of social responsibility disclosure is derived based on the Shari’ah Enterprise Theory. This research proposes a form of social responsibility disclosure for Islamic banks that show efforts to meet vertical accountability to God, and horizontal accountability to people and environment, as well as to consider the material and spiritual needs of stakeholders and to disclose information both qualitatively and quantitatively.